Maximum oxygen uptake and post-exercise recovery in professional road cyclists - Rutkowski, L.; Zaton, M.; Michalik, K. (Human Movement, 2016)
Purpose. The aim was to investigate the relationship between aerobic fitness as ascribed by maximum oxygen uptake (VO2max) and post-exercise recovery after incremental exercise to volitional exhaustion.